Conservative Treatment with Octreotide to Provide Early Recovery of Children with Esophageal Perforation - Karabulut, Ramazan; Turkyilmaz, Zafer; Sonmez, Kaan; Basaklar, Abdullah Can (The Thoracic and Cardiovascular Surgeon, 2018)
Background The effectiveness of nonoperative treatment of esophageal perforation (EP) in children with octreotide is highlighted.Methods Records of nine patients (seven boys and two girls with an average age of 5.83 ± 5.35 years) with EP were reviewed.Results EP developed in six patients during dilation of esophageal stenosis (five of six caused by caustic burns). In the other three patients, EP developed after nasogastric placement, after endotracheal intubation, and during endoscopy for foreign body. The symptoms consisted of dyspnea in four patients, tachypnea in seven patients, fever in six patients, chest pain in two patients, and abdominal pain in one patient. Two patients had pneumomediastinum, four patients had pleural effusion, one patient had subcutaneous emphysema, four patients had pneumothorax, and two patients had severe sepsis. Eight of the perforations resolved spontaneously. Therapy included cessation of oral feedings, implementation of proper antibiosis, parenteral and/or enteral nutrition by gastrostomy, and drainage of pleural effusions or mediastinal abscesses if required. Though not recommended by literature, octreotide was administered to these patients. Only one patient was operated in another clinic and was lost during follow-up. The length of hospitalization stay had a median of 11 ± 6.59 days, ranging between 5 and 28 days. If the patient who was operated and did not receive octreotide therapy is excluded, the median hospitalization was only 8 days (5 to 12 days). All patients in our series (except patient 8) survived and still have their native esophagus.Conclusion The initiation of octreotide treatment in the early period after diagnosis of EP without surgical intervention leads to early improvement in children.
Keywords: esophageal perforation; conservative management; octreotide